Investigation of the acid-mediated cyclisation of amide acetal for the synthesis of benzazepinone - Wong Phakhodee (2018)
On treatment with acids, the open-chained amide acetals (1) gave the 7,7 membered ring fused benzazepinones (4) via the bis-cyclisation. © 2008 The Japan Institute of Heterocyclic Chemistry.